The Effect of the Blended Learning Method on Madrasah Teachers at Madrasah Ibtidaiyah Private Cibeureum, Kertasari District, Bandung Regency - Yulita Silviany, Irma; Rachmah, Huriah; Nuranisa Dewi, Asri; ., Lasmanah (KnE Social Sciences, 2023)
Student learning motivation during the Covid-19 pandemic is very necessary, given the shift in learning methods as an effort to adjust the learning process to current conditions. In order to achieve the objectives in the learning process, motivation can be the overall driving force in students that can cause learning activities to occur. Learning motivation can be increased by adjusting digital-based teaching materials. Through interesting teaching materials, blended learning methods can be successful. The method used combines online and offline learning at the same time and is one of the impacts of the Covid-19 pandemic in the world of education that must be faced by Cibeureum Private Madrasah Ibtidaiyah teachers. Teaching materials that are usually made conventional, now have to be changed to digital-based. Training and mentoring are carried out as an innovation in the preparation of effective teaching materials and can accommodate blended learning needs and can increase student learning motivation. The training and mentoring were carried out over a period of 3 months, starting from January to March 2022 and there were 18 teacher participants. As a result, through this blended learning of training and mentoring, teachers are familiar with learning methods and can create and apply digital-based teaching materials to students during learning. Keywords: blended learning, madrasa teachers, digital-based learning